AN EXPERIMENTAL STUDY ON THE ADSORPTION OF PER AND POLYFLUOROALKYL SUBSTANCES (PFAS) BY SOIL-DERIVED COLLOIDAL PARTICLES - (:unkn) unknown (My University, 2024)
Per- and perfluoroalkyl substances (PFAS) represent a large group of synthesized chemicals that were produced at large scales from the 1930’s. As a result of their mass production, large scale commercial use and chemical stability, PFAS have been found ubiquitous within the environment and have been detected in human tissue, bone, and bodily fluids. There are growing concerns about the behavior and mobility of PFAS within the natural environment. Soil represents a major source of PFAS. Although it is well established that soil-derived colloids could facilitate the transport of a wide range of contaminants, there is a significant knowledge gap with regard to the interactions between PFAS and soil colloids. In this research, colloids were collected from intact soil cores that were drilled from agricultural fields located at Pound, WI. A series of experiments were performed to quantify the adsorption of 8 PFAS by the soil-derived colloids. Both synthesized rainwater and local groundwater were used for the adsorption experiments. The results showed that the linear adsorption model could be used to describe the PFAS adsorption behavior and the partitioning coefficient, Kd, were estimated from the experimental data. These measured PFAS adsorption parameters by soil-derived colloids can be used to develop mathematical models that aim at quantitatively describing PFAS transport within the vadose zone. It was also observed that PFAS adsorption on the soil colloids were stronger in groundwater than in rainwater suggested that colloid-bound PFAS from the vadose zone may continue to move with the colloidal phase rather than become released into the groundwater.
Keywords: Colloids; PFAS; Sorption